Comparative analysis of Anaerobic Baffled Reactor ( ABR ) and Moving Bed Biofilm Reactor ( MBBR ) for Domestic and Laundry Wastewater Treatment : Technical, Economic, and Enviromental Performance Assessment in Lamongan, East Java, Indonesia - Ramadhan, Iqbal (Dampak, 2025)
This study evaluates the treatment performance of Moving Bed Biofilm Reactor (MBBR) and Anaerobic Baffled Reactor (ABR) systems in treating domestic laundry wastewater in a tropical environment. Both reactors were operated for 90 days under optimized conditions, with MBBR achieving higher removal efficiencies for biochemical oxygen demand (BOD) and chemical oxygen demand (COD) at 94.6% and 95.2%, respectively, compared to ABR’s 92.6% and 91.7%. Nutrient removal was more effective in MBBR, particularly for ammonia (89%) and phosphate (96%). ABR demonstrated potential for biogas production, generating 126 m³/month, suggesting its viability as a sustainable energy source. However, both systems required post-treatment disinfection to reduce pathogenic bacteria to acceptable limits. Economic analysis indicated MBBR’s lower operational costs, while ABR offered advantages in energy recovery. This comparative study informs sustainable domestic wastewater management strategies in Lamongan, East Java, Indonesia. Keyword: Wastewater Treatment, Moving Bed Biofilm Reactor, Anaerobic Baffled Reactor, Domestic Laundry Wastewater, Biogas.